NORTH AMERICAN COLONYS OF THE BRITISH EMPIRE AND THE PROBLEM OF ENSURING THEIR SECURITY IN THE 1960S 19TH CENTURY - Simonenko E.S. (Вестник Брянского государственного университета, 2022)
The paper examines the process of transformation of the principles of Imperial defense in the North American colonies of the British Empire. It limits the chronological scope of the work to the 60s. XIX century, when the colonial possessions of Britain in North America received the status of a dominion, which assumed self-government, including in the field of defense. It traces the genesis of the idea of mutual obligations in the field of defense between the mother country and the North American colonies in the first half of the 19th century. It studies the strategic plans for the defense of Canadian territory, developed by British government and military experts at various levels. It formulates the views of W. Gladstone, which determined the policy of Imperial defense throughout the whole decade. It pays particular attention to the transformation of the maritime aspect of Imperial defense and its consequences for the North American colonies. It characterizes 60s 19th century by a weakening of the Anglocentric model of building relations with the North American colonies, where all the full obligations to ensure their security were assigned to the mother country. Henceforth, the colonies were to be responsible for the land defense of their territories. Thus, by the end of the 60s. 19th century finally took shape the trend of transition to the principle of mutual control and collective responsibility in the field of Imperial defense.